Exogenous, but not Endogenous Nitric Oxide Inhibits Adhesion Molecule Expression in Human Endothelial Cells - Qian, Jin; Fulton, David J. (Frontiers in Physiology, 2012)
Nitric oxide (NO) has many beneficial actions on the vascular wall including suppression of inflammation. The mechanism(s) by which NO antagonizes cytokine signaling are poorly understood, but are thought to involve inhibition of the pro-inflammatory transcription factor, NF-κB. NO represses nuclear translocation of NF-κB via the S-nitrosylation of its subunits which decreases the expression of target genes including adhesion molecules. In previous studies, we have shown that the intracellular location of endothelial nitric oxide synthase (eNOS) can influence the amount of NO produced and that NO levels are paramount in regulating the S-nitrosylation of target proteins. The purpose of the current study was to investigate the significance of subcellular eNOS to NF-κB signaling induced by pro-inflammatory cytokines in human aortic endothelial cells (HAECs). We found that in HAECs stimulated with TNFα, L-NAME did not influence the expression of intercellular adhesion molecule 1 (ICAM-1) or vascular cell adhesion molecular 1 (VCAM-1). In eNOS “knock down” HAECs reconstituted with either plasma membrane or Golgi restricted forms of eNOS, there was no significant effect on the activation of the NF-κB pathway over different times and concentrations of TNFα. Similarly, the endogenous production of NO did not influence the phosphorylation of IκBα. In contrast, higher concentrations of NO derived from the use of the exogenous NO donor, DETA NONOate, effectively suppressed the expression of ICAM-1/VCAM-1 in response to TNFα and induced greater S-nitrosylation of IKKβ and p65. Collectively these results suggest that neither endogenous eNOS nor eNOS location is an important influence on inflammatory signaling via the NF-κB pathway and that higher NO concentrations are required to suppress NF-κB in HAECs.